Implikasi Putusan Mahkamah Konstitusi Nomor 105/PUU-XXII/2024 Atas Kasus Pencemaran Nama Baik dalam Undang-Undang Informasi dan Teknologi Elektronik terhadap Kebebasan Berekspresi - Daffa Brilliandana Pratama; Prioni Rahmanda Saputri (Universitas Muhammadiyah Mataram, 2026)
Freedom of expression is a constitutional right guaranteed by the 1945 Constitution, but in practice, the implementation of the Electronic Information and Transactions Law (EIT Law) faces various challenges, including the fact that it is often viewed as a “rubber clause” due to overly broad interpretations, leading law enforcement officials and government officials to frequently use it to restrict or even silence public criticism. This study aims to analyze the implications of Constitutional Court Decision No. 105/PUU-XXII/2024 on law enforcement practices in defamation cases, as well as its impact on the protection of freedom of expression and legal certainty in Indonesia. The research method employed is a normative legal approach using a statutory framework and a case-based approach, supported by a literature review of primary and secondary legal sources. The research findings indicate that the Constitutional Court’s decision provides a constitutional interpretation that clarifies the scope of the provisions in Article 27A in conjunction with Article 45(4) of the ITE Law, particularly by limiting the phrase “another person” to individuals and interpreting “a matter” as an act that degrades a person’s honor or reputation. This interpretation narrows the scope for multiple interpretations and reduces the potential for abuse of the defamation provisions. Furthermore, this ruling has a positive impact in strengthening the protection of freedom of expression, reducing the potential for the criminalization of criticism, and enhancing legal certainty. Nevertheless, the implementation of the ruling still faces challenges, necessitating public awareness campaigns, regulatory harmonization, and the strengthening of a human rights-based approach among law enforcement officials so that the goal of protecting freedom of expression can be fully achieved.